Relationship between oral declaration on adherence to ivermectin treatment and parasitological indicators of onchocerciasis in an area of persistent transmission despite a decade of mass drug administration in Cameroon. Issue 1 (December 2015) - Wanji, Samuel; Kengne-Ouafo, Jonas; Esum, Mathias; Chounna, Patrick; Adzemye, Bridget; Eyong, Joan; Jato, Isaac; Datchoua-Poutcheu, Fabrice; Abong, Raphael; Enyong, Peter; Taylor, David
Abstract Background Onchocerciasis control for years has been based on mass drug administration (MDA) with ivermectin (IVM). Adherence to IVM repeated treatment has recently been shown to be a confounding factor for onchocerciasis elimination precisely in rain forest areas where transmission continues andLoa loa co-exists withOnchocerca volvulus . In this study, participants' oral declarations were used as proxy to determine the relationship between adherence to IVM treatment and parasitological indicators of onchocerciasis in the rain forest area of Cameroon with more than a decade of MDA. Methods Participants were recruited based on their IVM intake profile with the aid of a semi-structured questionnaire. Parasitological examinations (skin sniping and nodule palpation) were done on eligible candidates. Parasitological indicators were calculated and correlated to IVM intake profile. Results Of 2, 364 people examined, 15.5 % had never taken IVM. The majority (40.4 %) had taken the drug 1–3 times while only 18 % had taken ≥ 7 times. Mf and nodule prevalence rates were still high at 47 %, 95 % CI [44.9–49.0 %] and 36.4 %, 95 % CI [34.4–38.3 %] respectively. There was a treatment-dependent reduction in microfilaria prevalence (rs =−0.986, P = 0.01) and intensity (rs =−0.96, P = 0.01). The highest mf prevalence (59.7 %) was found in the zero treatment group and the lowest (33.9 %) in the ≥ 7 times treatment group (OR = 2.8; 95 % CI [2.09–3.74]; P < 0.001). Adults with ≥ 7 times IVM intake were 2.99 times more likely to have individuals with no microfilaria compared to the zero treatment group (OR = 2.99; 95 % CI [2.19–4.08], P < 0.0001). There was no clear correlation between treatment and nodule prevalence and intensity. Conclusion Adherence to ivermectin treatment is not adequate in this rain forest area whereL. loa co-exists withO. volvulus . The prevalence and intensity of onchocerciasis remained high in individuals with zero IVM intake after more than a decade of MDA. Our findings show that using parasitological indicators, reduction in prevalence is IVM intake-dependent and that participants' oral declaration of treatment adherence could be relied upon for impact studies. The findings are discussed in the context of challenges for the elimination of onchocerciasis in this rain forest area.